Nine takeaways from our reviews of COVID-19 education responses - Chuang, Rachel; Kaye, Tom; Koomar, Saalim; McBurnie, Chris; Moss Coflan, Caitlin (EdTech Hub, 2020)
Regular readers will know about our Helpdesk, the on-demand support service we provide for FCDO advisers and World Bank staff to help them make evidence-informed decisions. Since the onset of coronavirus, the Helpdesk team has responded to requests from 15 countries across Africa, Asia, and the Middle…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707876 2405685:28EHRZSK
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted